B-BBEE and its impact on the South African construction industry - Mpanza, Jabulile (School of Economics, 2016)
This dissertation seeks to critically investigate, examine and describe how four large South African construction companies have responded to and engaged with Broad-Based Black Economic Empowerment (B-BBEE). Using these companies as a case study, namely, Murray & Roberts, WBHO, Group Five and Basil Read, the paper highlights the extent to which BEE and later B-BBEE implementation has been effective in so far as meeting its objectives as articulated in the scorecard that is embedded in the Construction Sector Black Economic Empowerment Charter. Moreover, the study discusses the strategic changes undergone by each of the firms over a twenty year period (1994-2014) in their efforts to comply with policy, while remaining profitable and sustainable. Additionally, through an evaluation of these corporate strategies and various growth paths, the paper aims to articulate the approaches employed by each company in the face of a reformed political environment, assessing the common tendencies displayed in the industry. The paper consequently seeks to fill in the gaps in literature with regards to the strategies that large companies in the construction industry have gradually adapted in order to continue operating in a democratic South Africa. Thus, through its investigations, it addresses how and why the (1) industry designed and adapted its corporate strategies to fit the institutional arrangements, i.e. B-BBEE, (2), how the industry has responded and implemented BEE, and (3) how the industry has influenced the policy.